Own Pain Distress Mediates the Link Between the Lifestyle Facet of Psychopathy and Estimates of Pain Distress in Others - Brazil, Inti A.; Atanassova, Dimana V.; Oosterman, Joukje M. (Frontiers in Behavioral Neuroscience, 2022)
Psychopathy is a multifaceted personality construct entailing interpersonal-affective disturbances, antisocial traits, and a tendency to lead an erratic lifestyle. High levels of psychopathic traits have been linked to having an altered experience of pain, reduced responsivity to distress in others, and making poor moral choices that bring harm to others. In the context of moral decision-making, it is possible that the capacity to estimate the distress felt by others is linked to a limitation in the first-hand experience of distress, as the presence of psychopathic traits increases. We employed a model-based approach in a non-offender sample (n=174) to investigate whether pain-related distress mediated the links between facets of psychopathy and estimates of the pain distress potentially experienced by others. Participants judged the permissibility of moral dilemmas and rated how much pain distress they would experience while making such judgements, as well as how much pain distress they believed the ‘victims’ would feel as a result of the moral choice made by the participant. We found that ratings of own pain distress predicted beliefs about the distress others may experience, and higher scores on the lifestyle facet of psychopathy uniquely predicted lower estimates of own pain distress. Furthermore, own pain distress mediated the relationship between the lifestyle facet and beliefs about others’ distress. Finally, exploratory zero-order correlation analyses revealed that ratings of own pain distress decreased as the scores on multiple psychopathic traits increased. Only the lifestyle facet correlated in the negative direction with beliefs about others’ distress. Taken together, our findings suggest that beliefs about how much pain distress others may experience is indeed mediated by own pain distress, and that the tendency to lead an erratic lifestyle is linked to alterations in this mechanism.